High‐Energy Storage Density and Efficiency of (1−x)[0.94 NBT–0.06 BT]–xST Lead‐Free Ceramics. Issue 12 (12th October 2015) - Cao, Wenping; Li, Weili; Zhang, Tiandong; Sheng, Jie; Hou, Yafei; Feng, Yu; Yu, Yang; Fei, Weidong
Abstract: Using the component materials barium titanate (BaTiO3, BT), strontium titanate (SrTiO3, ST), and sodium bismuth titanate [(Na1/2 Bi1/2 )TiO3, NBT], anti‐ferroelectric lead‐free ceramics of (1− x )[0.94NBT–0.06BT]– x ST have been fabricated using conventional techniques. The microstructure, electrical properties, and energy‐storage performance of the obtained ceramics were investigated in detail. It was determined that the addition of ST can enhance the difference between the maximum polarization ( P max ) and remnant polarization ( P r ), resulting in the improvement of the energy‐storage properties. The maximum recoverable energy density of 0.98 J cm −3 with a relatively high efficiency of 82 % was achieved under 90 kV cm −1 at x =0.30, which also displayed excellent energy‐storage stability in the temperature range from room temperature to 120 °C. Abstract : Unleaded ceramics: Using the component materials barium titanate (BaTiO3, BT), strontium titanate (SrTiO3, ST), and sodium bismuth titanate [(Na1/2 Bi1/2 )TiO3, NBT], anti‐ferroelectric lead‐free ceramics of (1− x )[0.94NBT–0.06BT]– x ST are fabricated using conventional techniques. It is determined that the addition of strontium titanate (ST) enhances the difference between the maximum polarization ( P max ) and remnant polarization ( P r ), resulting in the improvement of energy‐storage properties.